Effects Of Zerumbone From Zingiber Zerumbet On Cervicalcancer-Induced Female Balb/C Mice - Devi Tailan, Nirmala (2007)
In the present study, the chemotherapeutic potential of zerumbone towards HeLa cell line and cervical cancer induced in female Balblc mice were investigated. The chemotherapeutic potential of zerumbone was compared with cisplatin, a commercial drug used to treat cervical cancer. The cytotoxicity of both zerumbone and cisplatin towards HeLa cell line were determined using MTT assay. The findings showed that the ICso value (* S.E.M) of zerumbone towards HeLa cell line was 11.3 * 0.2 pM, whilst the ICSO value of cisplatin was 7.5 * 0.3 pM. Both IC50 values for zerumbone and cisplatin fall within the very significant group based on the National Cancer Institute Standard. All the values are significant (P < 0.01). The HeLa cells were treated with ICso concentration of zerumbone and cisplatin respectively for morphological analysis using inverted microscopy. The results showed significant growth retardation in HeLa iii cells exposed to zerumbone and cisplatin at 24,48 and 72 hours, whilst the control cells are well spread and confluent. Pregnant female Balblc mice were exposed to Diethylstilbestrol (DES) at 13'~to 1 8 '~d ay of gestation. The progeny of the DESexposed mothers developed cervical intra-epithelial neoplasia. These progenies were divided into 4 groups and were either given treatment with normal saline, 8 mglkg zerumbone, 16 mg/kg zerumbone and 10 mg/kg cisplatin. The mice were sacrificed following the treatments and their cervical tissues subjected to histological examination, TUNEL Assay and immunohistochemistry. The histological examination revealed that both zerumbone and cisplatin treatments were able to inhibit the progression of cervical dysplasia fiom becoming more severe dysplasia (CIN 3). In the mice treated with normal saline, the dysplasia had progressed to CIN 3 (severe dysplasia). The TUNEL assay micrographs showed that there was no apoptosis in the cervical tissue of the normal saline treated mice compared to the cervical tissue of mice treated with zerumbone and cisplatin, where abundant apoptotic cells were noticed. The levels of serum IL-6 were suppressed in mice treated with zerumbone and cisplatin. In contrast, mice treated with normal saline showed elevated level of serum IL-6. Immunohistochemistry study demonstrated that the production level of membrane bound IL-6 receptor had been suppressed by the treatment of zerumbone and cisplatin compared to mice treated with normal saline which had a higher concentration of membrane bound IL-6 receptors. This showed that both zerumbone and cisplatin act in a similar manner in vivo and in vitro. In conclusion, it is suggested that zerumbone, a plant derived compound, could be explored as a new anti cancer agent for treating cervical cancer in the future.